EKSISTENSI PEMENTASAN TARI BARONG DAN RANGDA - Sumiartha, I Nengah Wenten (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2022)
This writing about the existence of barong and rangda dance performances is based on social life, the people of Tanah Embet Hamlet have a high sense of brotherhood, mutual respect between residents and one another. So there are rarely disputes between residents because between residents there is still a relative relationship. Therefore, research on the performance of Barong and Rangda Dances is considered necessary to know the history, processions, and public perceptions of the performance of Barong and Rangda Dances. From the results of the study, data were obtained that the staging of Barong and Rangda Dances is an ancestral heritage, where before the stage of Barong and Rangda Dance, the hamlet of Tanah Embet was once hit by disease outbreaks and drought stands for. Barong and Rangda Dance staging procession, first, preparation activities for facilities and upakara were carried out, praying together at the Patokan temple, carrying out the staging ceremony, and continued with the performance of Barong and Rangda Dances. After the completion of the storage ceremony at pemaksan temple. The people of Tanah Embet have the same perception of barong and rangda dance performances, but the most important purpose of staging Barong and Rangda dance is to reject bala (disease), beg for welfare, and prosperity.